2021
DOI: 10.1002/aelm.202100979
|View full text |Cite
|
Sign up to set email alerts
|

Super Electrical Insulating Materials Based on Honeycomb‐Inspired Nanostructure: High Electrical Strength and Low Permittivity and Dielectric Loss

Abstract: The high breakdown field strength is the most important index to evaluate the performance of insulating materials. It is theoretically found that the breakdown field strength of dielectric samples can be significantly improved by up to 1–2 orders of magnitude by constructing nanopore structures. Thus, bridged silsesquioxane super electrical insulating materials (BSSEIM) are developed with nanosized pore structures and their extremely high electrical insulation performance is realized. The results indicate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that the collision ionisation can be inhibited by nanosized pore structures with pore size close to or slightly larger than the average electron free path [15, 16]. It is noted that OTS coating has a large number of pores and pits at the level of 100 nm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the collision ionisation can be inhibited by nanosized pore structures with pore size close to or slightly larger than the average electron free path [15, 16]. It is noted that OTS coating has a large number of pores and pits at the level of 100 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Since the sandpaperpolishing and sandblasting surface treatment methods used in existing researches mainly produce micron-scale topography, the existing research mainly focuses on the effect of micronscale morphology. Lei et al [15] and Sima et al [16] found that the breakdown voltage can be significantly improved by preparing porous-structure insulating materials with pores from 10 nm to one-micron level, in which the electron avalanche process is suppressed by nanoscale pores with size below or equal to the mean free path of electrons. Similarly, the flashover strength may also be improved by structuring surface topography on the scale of hundreds of nanometres, but to the best of our knowledge, the effect of nanoscale topography is still rarely explored.…”
Section: Introductionmentioning
confidence: 99%
“…The mean free path of electrons is one of the main factors affecting the collisional ionization of gas molecules. Previous studies have shown that the collision ionization can be effectively inhibited by porous structures with pore diameter close to or slightly larger than the mean free path of electrons [21,23,24]. The mean free path of electrons can be expressed by [39]:…”
Section: Mechanism Of Flashover Strength Improvementmentioning
confidence: 99%
“…However, due to the complex correlation between matrix and filler of composite coatings, the role of nanoscale morphology cannot be clearly distinguished. Xin et al [23] and Sun et al [24] found that porous materials with pore diameter close to the electron mean free path could improve the breakdown strength owing to the inhibition effect on collision ionization and avalanche breakdown. The influence of pore diameter on breakdown performance is clarified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation